Rapid Low‐Temperature 3D Integration of Silicon Nanowires on Flexible Substrates. Issue 32 (5th May 2015) - Kim, Yoonkap; Kim, Han‐Jung; Kim, Jae‐Hyun; Choi, Dae‐Geun; Choi, Jun‐Hyuk; Jung, Joo‐Yun; Jeon, Sohee; Lee, Eung‐Sug; Jeong, Jun‐Ho; Lee, Jihye
<x xml:space="preserve">Abstract</x> The vertical integration of 1D nanostructures onto the 2D substrates has the potential to offer significant performance gains to flexible electronic devices due to high integration density, large surface area, and improved light absorption and trapping. A simple, rapid, and low temperature transfer bonding method has been developed for this purpose. Ultrasonic vibration is used to achieve a low temperature bonding within a few seconds, resulting in a polymer‐matrix‐free, electrically conducting vertical assembly of silicon nanowires (SiNWs) with a graphene/PET substrate. The microscopic structure, and mechanical and electrical characteristics of the interface between the transferred SiNW array and graphene layer are subsequently investigated, revealing that this creates a mechanically robust and electrically Ohmic contact. This newly developed ultrasonic transfer bonding technique is also found to be readily adaptable for diverse substrates of both metal and polymer. It is therefore considered as a valuable technique for integrating 1D vertical nanostructures onto the 2D flexible substrates for flexible photovoltaics, energy storage, and water splitting systems.